Social Engagement With Cognitive Function In The Elderly At Posyandu Lanjut Usia Mekar Sari, RW V, Mojo, Surabaya - Dian, Trifena; Maramis, Margarita M.; Maria, Edith (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: The increased number of the elderly dominates the improvement of lifeexpectancy of age in Indonesia. This condition is caused by a variety of health problems, including the decline of cognitive function. One of the risk factors for cognitive decline is social engagement. Social disengagement was associated with lower cognitive function. Aim: The objective of this study was to determine the correlation between social engagement and cognitive function in the elderly at Posyandu Lanjut Usia Mekar Sari, RW V, Mojo, Surabaya. Method: This research is an observational analysis with a cross-sectional study design. The population in this research is all elderly in Posyandu Lanjut Usia Mekar Sari, RW V, Mojo, Surabaya. The sample of this study is the elderly aged above 60 years old. The sampling research in this report is Consecutive Sampling Result: The result of the Rank Spearman correlation test hold the probability value as (Sig.) 0.201. The test showed a result of p > ? (? = 0.05) Conclusion: There was no significant correlation between social engagement and cognitive function in the elderly at Posyandu Lansia Mekar Sari, RW V, Mojo, Surabaya